Analysis of Total Suspended Solid Distribution and Its Effect to the Fertility of Marine Waters Around Fish Auction Place (TPI) Dumai - Situmorang, Nesi Silvia; Rifardi, Rifardi; Siregar, Yusni Ikhwan (Journal of Coastal and Ocean Sciences, 2021)
This study aims to determine the distribution of total suspended solid concentration (TSS) in the waters around TPI Dumai. Water samples were taken from 12 sampling point from the waters during high and low tides to determine TSS concentration. The concentration of total suspended solids ranges from 60-130 mg/l. The concentration is relatively higher (>80 mg/l) in the area that is close to residential areas and TPI. The highest concentration of total suspended solids was 117 mg/l found in waters with a depth of 1-3 m, while the lowest was 81 mg/l found at the sampling point of 5,9. The distribution of chlorophyll-a concentration is relatively higher around the coast which is around 0.476-0.178 mg/l, and it's lower off the shore which is around 0.080-0.090 mg/l. The chlorophyll-a concentration is lower in waters far from the coast because there is no direct nutrient supply from the land. The regression analysis indicate that Tss and chlorophyll-a has a weak relationship between the two variables relatively weak but they are still affecting each other